Atherogenic Index of Plasma and Anthropometric Measurements among Osteoporotic Postmenopausal Sudanese Women: Possible Risk for Cardiovascular Disease - Abdelgadir Elmugadam; Ghada A. Elfadil; Abdalrahman Ismail Hamad; Ahlam Badreldin El Shikieri; Mawahib Aledrissy; Hisham N. Altayb (Journal of Aging Research)
Introduction. Data examining the health of menopausal women and the prevalence of osteoporosis remain to be limited in Africa, especially in sub-Saharan countries. Thus, in this current study, we aimed to assess the atherogenic index of plasma (AIP) and anthropometric measurements of osteoporotic postmenopausal women and determine their risk for cardiovascular disease (CVD). Methods. This is a cross-sectional, community-based study. Postmenopausal women (n = 300), aged ≥45 years, were recruited from Khartoum state, Sudan. Dual-energy X-ray absorptiometry was used to assess bone density. Weight, height, and waist circumference were measured twice. Fasting blood samples (5 ml) were collected to determine total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C). AIP was calculated as an indicator of CVD risk. Results. The mean age of the postmenopausal women was 61.6 ± 10.2 years (range 47–90 years). Women (n = 80) had the normal T-score, and an equal number had osteoporosis (n = 110) and osteopenia (n = 110). The prevalence of osteoporosis was 36.7%. Many postmenopausal women with normal T-scores suffered from general (71.2%) and central (94%) obesity. Postmenopausal women had high TC (24.4%), TG (25.6%), LDL-C (13.7%), and low HDL-C (76.0%) levels. Osteoporotic women (36.4%) were found to have a medium to high risk of CVD as determined by AIP. Women with normal T-scores had a higher number of CVD risk factors. A positive correlation was noted between AIP and TC among osteopenic (r = 0.292; P=0.002) and osteoporotic women (r = 0.265; P<0.001). Conclusion. Osteoporosis was prevalent among Sudanese postmenopausal women who also had an increased risk for CVD. Public health education about osteoporosis and CVD risk is thus recommended.